Determining the Correlations between Geo-chemical Speciation of Heavy Metals in Surface Sediments and Their Concentrations in Giant Mudskipper - Buhari, Tijjani Rufa’i; Ismail, Ahmad (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
Surface sediments and giant mudskipper (Periophthalmodon schlosseri) were collected in August and September 2008 and in March and June 2010 from six sampling sites in the west coast of Peninsular Malaysia to assess heavy metals accumulation in giant mudskipper. The aim of the present study was to assess heavy metals concentration in giant mudskipper (Periophthalmodon schlosseri) and their correlations with different geochemical fractions of sediments. Sequential extraction technique was used to fractionate the sediments into four different geo-chemical fractions; easily, freely or leachable and exchangeable (EFLE), acid reducible, oxidizable organic and resistant fractions. Heavy metals concentrations (Cu, Zn, Pb, Cd and Ni) in the surface sediments and giant mudskipper were determined by using air acetylene flame atomic absorption spectrophotometer (AAS) Perkin Elmer Analyst 800. The results of Pearson’s correlation analyses showed that metal concentrations in the tissues of P. schlosseri were significantly correlated (p < 0.01 or p < 0.05), correlations were observed between Cu in P. schlosseri and Cu in the sediment (oxidisable organic, resistant and total Cu), Zn in P. schlosseri and Zn in the sediment (EFLE and total Zn), Pb in P. schlosseri and Pb in the sediment (with all the four fractions of Pb), Cd and Ni in P. schlosseri and Cd and Ni in the sediment (with all fractions of Cd and Ni except acid-reducible Cd and Ni) which might suggest the use of P. schlosseri as a biomonitoring agent for heavy metals pollution in the west coast of Peninsular Malaysia.